The ARE-dependent mRNA-destabilizing activity of BRF1 is regulated by protein kinase B - Schmidlin, Martin (Nature Publishing Group, 2004)
Butyrate response factor (BRF1) belongs to the Tis11 family of CCCH zinc-finger proteins, which bind to mRNAs containing an AU-rich element (ARE) in their 3′ untranslated region and promote their deadenylation and rapid degradation. Independent signal transduction pathways have been reported to stabilize ARE-containing transcripts by a process thought to involve phosphorylation of ARE-binding proteins. Here we report that protein kinase B (PKB/Akt) stabilizes ARE transcripts by phosphorylating BRF1 at serine 92 (S92). Recombinant BRF1 promoted in vitro decay of ARE-containing mRNA (ARE-mRNA), yet phosphorylation by PKB impaired this activity. S92 phosphorylation of BRF1 did not impair ARE binding, but induced complex formation with the scaffold protein 14-3-3. In vivo and in vitro data support a model where PKB causes ARE-mRNA stabilization by inactivating BRF1 through binding to 14-3-3.